2004
DOI: 10.1023/b:joec.0000017975.16399.c3
|View full text |Cite
|
Sign up to set email alerts
|

Acquired and Partially De Novo Synthesized Pyrrolizidine Alkaloids in Two Polyphagous Arctiids and the Alkaloid Profiles of Their Larval Food-Plants

Abstract: The profiles of pyrrolizidine alkaloids (PAs) in the two highly polyphagous arctiids Estigmene acrea and Grammia geneura and their potential PA sources in southeastern Arizona were compiled. One of four species of Boraginaceae, Plagiobothrys arizonicus, contained PAs; this is the first PA record for this plant species. The principle PA sources are Senecio longilobus (Asteraceae) and Crotalaria pumila (Fabaceae). The known PA pattern of S. longilobus was extended; the species was found to contain six closely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 17 publications
2
46
1
2
Order By: Relevance
“…Because PAs and PANOs do not show characteristic ultraviolet (UV) spectra (exhibiting only a non-specific UV-maximum of 214 nm), simple UV detection is of limited value. However, LC techniques are frequently and successfully used to purify PAs for structural identification including the enantioseparation of isomers like intermedine/lycopsamine (Hartmann et al, 2004;Pawar et al, 2010). Recently, a HPLC approach was published where retronecine-type PAs are converted by pre-column derivatisation to a common core structure derivative (7-methoxy-1-methoxymethyl-6,7-dihydro-5H-pyrrolizine) and analysed by reverse phase HPLC with photodiode array detection (HPLC-diode array detection (DAD) (absorption maximum at 223 nm)).…”
Section: Liquid Chromatography (Lc) and Liquid Chromatography-(tandemmentioning
confidence: 99%
“…Because PAs and PANOs do not show characteristic ultraviolet (UV) spectra (exhibiting only a non-specific UV-maximum of 214 nm), simple UV detection is of limited value. However, LC techniques are frequently and successfully used to purify PAs for structural identification including the enantioseparation of isomers like intermedine/lycopsamine (Hartmann et al, 2004;Pawar et al, 2010). Recently, a HPLC approach was published where retronecine-type PAs are converted by pre-column derivatisation to a common core structure derivative (7-methoxy-1-methoxymethyl-6,7-dihydro-5H-pyrrolizine) and analysed by reverse phase HPLC with photodiode array detection (HPLC-diode array detection (DAD) (absorption maximum at 223 nm)).…”
Section: Liquid Chromatography (Lc) and Liquid Chromatography-(tandemmentioning
confidence: 99%
“…It seems unlikely that it is absorbed directly from the plant as only a small proportion of eggs is in contact with the host. The results suggest that it may be of female origin, either by direct synthesis or via sequestration of host plant defences (Dobler et al, 1998;Barker et al 2002;Hartmann et al, 2004) or both as found for the monoterpene myrcene in the bark beetle, Ips pini (Seybold & Tittiger, 2003) or from male origin at time of mating (Bali et al, 1996;Gillot, 2003).…”
Section: Discussionmentioning
confidence: 79%
“…14,15,[27][28][29] We assigned the absolute stereochemistry of PAs based only in retention index of chiral PAs reported in the literature. 20,27 Chemical defense of Scearctia figulina: predation bioassays…”
Section: Pyrrolizidine Alkaloid Analysismentioning
confidence: 99%